2017
DOI: 10.1253/circj.cj-17-0440
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing in Heart Failure ― A Therapeutic Dilemma ―

Abstract: for their deployment can be advocated (Table). However, the promise of observational studies and randomized trials of small size and duration describing a beneficial effect of treating SDB in HF via positive airway pressure (PAP) was not realized in 2 recent randomized outcome-driven trials: SAVE, which evaluated the cardiovascular effect of treating OSA in a cohort without HF, 7 and SERVE-HF, which reported the results of a strategy of random allocation of minute-ventilation-triggered adaptive servo-ventilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The principal risk factors for central sleep apnea (CSA) were male gender, atrial fibrillation, age > 60 years, and hypocapnia (PCO2 < 38 mmHg). Subsequently, similar prevalences, based on lower or higher diagnostic thresholds, were documented in German, British, Japanese and American heart failure cohorts (60). Longitudinal studies revealed 453 the prognostic importance of concurrent sleep apnea: in our patients with ischemic cardiomyopathy but no or only mild sleep apnea, 3-year survival was approximately 83%, whereas if moderate to severe sleep apnea was diagnosed and treatment declined, 3-year survival was approximately 48% (adjusted hazard ratio P=0.04) (61).…”
Section: Sympathetic Nervous System In Human Heart Failure R-00143-2021 R1mentioning
confidence: 68%
See 1 more Smart Citation
“…The principal risk factors for central sleep apnea (CSA) were male gender, atrial fibrillation, age > 60 years, and hypocapnia (PCO2 < 38 mmHg). Subsequently, similar prevalences, based on lower or higher diagnostic thresholds, were documented in German, British, Japanese and American heart failure cohorts (60). Longitudinal studies revealed 453 the prognostic importance of concurrent sleep apnea: in our patients with ischemic cardiomyopathy but no or only mild sleep apnea, 3-year survival was approximately 83%, whereas if moderate to severe sleep apnea was diagnosed and treatment declined, 3-year survival was approximately 48% (adjusted hazard ratio P=0.04) (61).…”
Section: Sympathetic Nervous System In Human Heart Failure R-00143-2021 R1mentioning
confidence: 68%
“…Our subsequent long-term trial of treating heart failure patients with co-existing CSA was neutral (78), principally because in ~40% enrolled, conventional CPAP failed to suppress apnea (79). We are now exploring, in a multinational randomized clinical trial, the impact of long-term adaptive servo-ventilation therapy on survival and cardiovascular hospitalization of patients with heart failure and either OSA or CSA (60,80).…”
Section: Sympathetic Nervous System In Human Heart Failure R-00143-2021 R1mentioning
confidence: 99%
“…It will be possible to test prospectively whether responses to ASV therapy differ between the positive and negative forms of CSR-CSA in the setting of the ADVENT-HF trial [11,35]. This randomized trial is examining the effects of peak flow triggered ASV on morbidity, mortality and cardiac structure and function [36] in HFrEF patients with either CSR-CSA or OSA. Reduction in LV workload is a mainstay of HFrEF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to determine whether managing SDB improves the prognosis of patients with SDB. Several studies in patients with CAD 106) or HF 107, 108) are ongoing and their results are expected.…”
Section: Interpretation Of Recent Randomized Clinical Trials and Futumentioning
confidence: 99%